PROFITABILITY AND COMPETITIVENESS OF CORN FARMING IN GOWA REGENCY, SOUTH SULAWESI PROVINCE, INDONESIA - Natsir, Mohammad; Mardiyati, Sri (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Corn is a multifunctional crop that is useful for food, feed, fertilizer, and biofuel. The increasing demand for corn commodities requires an increase in profitability and competitiveness, so that corn farming will be sustainable. The purpose of this research was to examine the profitability and competitiveness of corn farming in Bontonompo District, Gowa Regency. The survey method was employed in this investigation. Data collection methods include observation and interviews. The sampling technique used was purposive sampling, namely deliberately selecting farmers who were trying to plant corn in paddy fields in the second planting season (MT2), and farmers who were active in farmer group activities, so that a sample of 45 respondents was obtained. There are two types of research data: primary data and secondary data. Profitability analysis and PAM (Policy Analysis Matrix) are two data analysis methodologies. According to the findings of this study, the private profit or financial profit of corn farming in Bontonompo District, Gowa Regency, is Rp 7,731,314.10 per hectare, while the social profit or economic profit is Rp 8,924,460.07 per hectare. Corn farming has a financial feasibility ratio of 2,531, whereas it has an economic feasibility ratio of 2,453. Corn growing in Gowa Regency has a reasonably high level of competitiveness, as evidenced by a private cost ratio (PCR) of 0.333 and a domestic resource cost ratio (DRCR) of 0.293.